2020
DOI: 10.48550/arxiv.2010.08079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revisiting Shao and Sokal's $B_2$ index of phylogenetic balance

Abstract: Measures of phylogenetic balance, such as the Colless and Sackin indices, play an important role in phylogenetics. Unfortunately, these indices are specifically designed for phylogenetic trees, and do not extend naturally to phylogenetic networks (which are increasingly used to describe reticulate evolution). This led us to consider a lesser-known balance index, whose definition is based on a probabilistic interpretation that is equally applicable to trees and to networks. This index, known as the B 2 index, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The balance of phylogenetic trees is a well studied topological characteristic. The balance for phylogenetic networks is recently revisited in [3], where the B 2 balance for phylogenetic networks [46] is reintroduced. The B 2 balance is an index based on the entropy of probability distribution on leaf nodes.…”
Section: Network Balancementioning
confidence: 99%
See 1 more Smart Citation
“…The balance of phylogenetic trees is a well studied topological characteristic. The balance for phylogenetic networks is recently revisited in [3], where the B 2 balance for phylogenetic networks [46] is reintroduced. The B 2 balance is an index based on the entropy of probability distribution on leaf nodes.…”
Section: Network Balancementioning
confidence: 99%
“…For phylogenetic trees, it is well discussed which stochastic process generates phylogenetic trees that resemble trees reconstructed from data [6], and random tree generators are well compared from different points of view [48,40,12,3]. However, as increasingly many network generators are developed, there is a lack of discussion about the differences and similarities of generated random networks.…”
Section: Introductionmentioning
confidence: 99%
“…While Shao and Sokal [73] originally defined the B 2 index for trees, Bienvenu et al [7] found that, due to its probabilistic interpretation, it is applicable to networks as well. In its definition, the value p x is the probability of reaching leaf x when starting at the root and assuming equiprobable branching at each inner vertex.…”
Section: B 2 Indexmentioning
confidence: 99%
“…More precisely, the B 2 index is the Shannon entropy of the probability distribution (p x ) x∈VL(T ) . Bienvenu et al [7] described this vividly as letting water drip down from the root along the edges and then measure how evenly it is distributed among the leaves. Shao and Sokal [73] did not state what logarithm base to use (possibly log 10 considering their example), but Bienvenu et al [7] pointed out that base 2 is convenient when working with binary trees.…”
Section: B 2 Indexmentioning
confidence: 99%
See 1 more Smart Citation